2017
DOI: 10.1080/10942912.2017.1337791
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and microstructural properties of wheat flour dough systems added with potato granules

Abstract: It is expected to improve the utilization of potatoes and enhance the nutritional value of traditional staple food by adding a certain proportion of potato granules to wheat flour in developing noodles and bread. This research aimed to investigate the effects of potato granules on the rheological properties and microstructure of wheat flour dough samples. The rheological properties of dough samples with various proportions of potato granules (0, 20, 25, 30, 35, and 40 wt%) were determined using a rheometer. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 37 publications
(43 reference statements)
4
21
1
Order By: Relevance
“…It indicates that the incorporation of the inulin granules decreased the continuity of the protein structure on the dough surfaces and enlarged the hollows and voids. The similar observation was reported by Xu, Hu, Liu, Dai, and Zhang (2017) for potato granules added wheat flour dough.…”
Section: Resultssupporting
confidence: 89%
“…It indicates that the incorporation of the inulin granules decreased the continuity of the protein structure on the dough surfaces and enlarged the hollows and voids. The similar observation was reported by Xu, Hu, Liu, Dai, and Zhang (2017) for potato granules added wheat flour dough.…”
Section: Resultssupporting
confidence: 89%
“…Gluten is the major protein source in wheat flour, which is extremely important to form the viscoelastic structure of dough (Mirsaeedghazi, Emam-Djomeh, & Mousavi, 2008). Rheological properties are closely associated with the viscoelasticity and mixing tolerance of dough, which also provide an important reference for the processing properties of flour (Xu, Hu, Liu, Dai, & Zhang, 2017). The rheological properties of dough not only determine the processing characteristics during the manufacture of dough-based products but also affect the quality of final products (Mccann, Gall, & Li, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…We have confirmed that potato noodles made from potato flour and wheat flour mixtures have higher nutritional values than the normal wheat noodles (Xu, Hu, Dai, et al, ). We also found that the addition of potato flour has a negative effect on edible quality of noodle, due to its diluting effect on gluten network (Xu, Hu, Liu, et al, ). In order to improve the edible quality and in the meantime to maintain the high nutritional value of potato noodle, 35% potato flour and 4% of gluten powder can be used to substitute wheat flour.…”
Section: Introductionmentioning
confidence: 92%
“…In China, the consumption of noodles as a daily staple food is one of the most distinguished features of oriental traditions (Rytel, ). Our group has long‐term experience in research and development in the area of staple potato products, particularly potato noodles (Huang, Xu, Hu, Dai, & Zhang, ; Tan et al, ; Xu, Hu, Dai, et al, ; Xu, Hu, Liu, Dai, & Zhang, ; Zhang, Xu, Wu, Hu, & Dai, ). We have confirmed that potato noodles made from potato flour and wheat flour mixtures have higher nutritional values than the normal wheat noodles (Xu, Hu, Dai, et al, ).…”
Section: Introductionmentioning
confidence: 99%